Novel Regulation Mechanism of Adrenal Cortisol and Dhea Biosynthesis Via the Endogen Erad Inhibitor Small Vcp-Interacting Protein - İlhan, Recep; Yılmaz, Sinem; Üner, Göklem; Üner, Göklem; Yılmaz, Sinem; Atalay Sahar, Esra; Çaylı, Sevil; Erzurumlu, Yalçın; Gözen, Oğuz; Ballar Kırmızıbayrak, Petek (Nature Publishing Group, 2022)
Endoplasmic reticulum-associated degradation (ERAD) is a well-characterized mechanism of protein quality control by removal of misfolded or unfolded proteins. The tight regulation of ERAD is critical for protein homeostasis as well as lipid metabolism. Although the mechanism is complex, all ERAD branches converge on p97/VCP, a key protein in the retrotranslocation step. The multifunctionality of p97/VCP relies on its multiple binding partners, one of which is the endogenous ERAD inhibitor, SVIP (small VCP-interacting protein). As SVIP is a promising target for the regulation of ERAD, we aimed to assess its novel physiological roles. We revealed that SVIP is highly expressed in the rat adrenal gland, especially in the cortex region, at a consistently high level during postnatal development, unlike the gradual increase in expression seen in developing nerves. Steroidogenic stimulators caused a decrease in SVIP mRNA expression and increase in SVIP protein degradation in human adrenocortical H295R cells. Interestingly, silencing of SVIP diminished cortisol secretion along with downregulation of steroidogenic enzymes and proteins involved in cholesterol uptake and cholesterol biosynthesis. A certain degree of SVIP overexpression mainly increased the biosynthesis of cortisol as well as DHEA by enhancing the expression of key steroidogenic proteins, whereas exaggerated overexpression led to apoptosis, phosphorylation of eIF2α, and diminished adrenal steroid hormone biosynthesis. In conclusion, SVIP is a novel regulator of adrenal cortisol and DHEA biosynthesis, suggesting that alterations in SVIP expression levels may be involved in the deregulation of steroidogenic stimulator signaling and abnormal adrenal hormone secretion.
This research was funded by the Scientific and Technological Research Council of Turkey (TUBITAK, SBAG-116S444) and by Ege University internal funds (16/ECZ/006). We thank the Pharmaceutical Sciences Research Centre (FABAL, Ege University, Faculty of Pharmacy) and Biotechnology and Bioengineering Application and Research Centre (BIYOMER, İzmir Institute of Technology) for equipment support, Burcu ERBAYKENT TEPE-DELEN, Selin GÜNAL, and Aysegül KAYMAK for their technical assistance and scientific support.
Keywords: ERAD; Proteins; DHEA biosynthesis